Telenovela: técnicas de criação do popular e do massivo - Rocha, Marlúcia Mendes da (2009)
A study of the cultural meanings of Brazilian soap operas, - the survey of the cultural and sign construction of the Brazilian soap opera, a tele-visual novel or series leading to convergence and a miscegenated culture. We propose analyzing soap operas as a hypertext script, given its plurality in reading, remitting us to: radio, review theater, photography, cinema, video and fotonovela, conditioned in such a way that it tells specific tales on the life and objects of Brazilían culture. Methodologically, we will work on concepts of the cultural cartography of Jesus Martín-Barbero, Michel de Certeau and Boaventura de Sousa Santos; with Yuri Lotman's culture semiotics, in which the dialogue between cultural complexes permeates the borderlines between art and culture, creating spaces that give way to senses that move dynamically with relation to the inter-textual and hybridization of elements, based on the studies on the cultural miscegenation of Laplantine and Naus, Serge Gruzinski and Amálio Pinheiro that lead to assimilation in the semiotic-cultural creations of medias, partícularly television. For this purpose, the survey will be carried out vertically to the analysis of the soap opera Que Rei sou eu (What King am I), by Cassiano G. Mendes, from Globo TV, 1989, verifying his influence in the process to choose the president elect through a direct vote, and the soap opera Água na Boca, (Mouth Watering) by Marcos Lazarini, TV Bandeirantes, 2008, given its approach on the assimilation of different cultures